Supply Chain Management Analysis of Coffee Beans : A Case Study in Ulu Belu District, Tanggamus Regency - Azra Wijaya; Rr Erlina (Management Dynamics: International Journal of Management and Digital Sciences, 2025)
Coffee is an important commodity in Indonesia with high economic value. In Ulu Belu District, coffee distribution through long channels causes high distribution costs, so supply chain management (SCM) is needed to improve efficiency. This study aims to measure the cost efficiency and effectiveness of coffee distribution using qualitative descriptive analysis method. The results showed that coffee marketing efficiency in Channel I amounted to 11.98%, and Channel II amounted to 11.92%, both classified as efficient. Delivery accuracy was also high, with Channel I reaching 98.89%, while Channel II was 85.83%. Channel II is more cost-effective despite Channel I being more effective in delivery. Cost-efficiency is important because coffee is a perishable product, and weather-related delays are rare. Channel I, which involves many members, increases distribution costs, so Channel II is recommended for optimal efficiency. It is suggested that improvements to transportation infrastructure, road access, and storage facilities at trader locations can increase distribution efficiency, maintain coffee quality, and reduce losses.